Environmental effects on germination and seedling emergence of weedy rice - Nornasuha, Yusoff; Mohammad Moneruzzaman, Khandaker; Muhd Furqan, Abdul Rahman; Norhafiza, Yaakob (2019)
The objective of this study is to determine the germination and growth of weedy rice seedlings that were grown under four different environmental conditions simulated in either growth chamber or room conditions. Photoperiod (24 h light, 24 h dark, 12 h light-dark), drought (0, 5, 10, 20 %) and temperature (25, 30, 35, 40 °C) effects were tested in growth chamber while the flooding depth (0, 2.5, 5, 10 cm) effects was tested in room condition. Germination percentage was not significantly affected (p > 0.05) by either of the environmental factors except for flooding depth at 10 cm. Temperature treatment specifically at 30 °C showed a pronounced effect on hypocotyl length, radicle length and root-shoot ratio compared to other temperature range. Highest hypocotyl length and root-shoot ratio were recorded in 10 % drought treatment and longest radicle length obtained in control treatment. Meanwhile, a continuous dark condition in photoperiod treatment showed the highest hypocotyl length in comparison to 24 hours of light and alternate 12 hours of light and dark. Highest radicle length and root-shoot ratio were obtained in 24 hours of light and 12 hours alternate light and dark respectively. Growth of weedy rice exhibited a declining trend in increasing flooding depth. The result of this study suggests that germination was retarded by deep flooding. Temperature and flooding depth affects the vegetative growth of weedy rice the most and sustained growth was observed at higher temperature regime. The information gained from this study may be useful in assessing the growth performance of weedy rice in relation to cultivated rice, and further helps in developing effective Malaysian weedy rice control strategies.